Implementation of Guidance and Counseling Programs in Secondary Schools: A Study of Components, Challenges, and Strategies for Strengthening - Septia Rahmawati; Ni Kadek Yulanda Kusuma Wardhani; Kadek Jessika Ardeliana; Zahra Zalsabilha; Aziz Zulazmi Samsudin (PSDKU Guidance and Counseling, Universitas Negeri Surabaya, 2026)
This study aims to comprehensively examine the implementation of the Guidance and Counseling (BK) program in a senior high school in Singaraja Bali, including its core components, challenges, and strategies for improvement. This research employed a descriptive qualitative approach. Data were collected through semi- structured interviews and supported by participatory observation and literature review. Data analysis followed an interactive model consisting of data reduction, data display, and drawing conclusions. The findings indicate that the BK program has been implemented systematically through planning, implementation, and evaluation processes, aiming to support students’ optimal development in personal, social, academic, and career domains. The implementation is supported by four main components: the professionalism of the school counselor, the integration of the Merdeka Curriculum emphasizing character education, collaborative practices with internal and external stakeholders, and continuous evaluation using various assessment tools such as sociometry and psychological tests. However, several challenges were identified, including a high administrative workload, situational and reactive service delivery, limited student understanding of evaluation instruments, and low parental involvement. Additionally, the evaluation process has not been fully optimized due to limited competence and a lack of professional training among counselors. Therefore, this study recommends strengthening the BK program through more systematic planning, flexible and adaptive service delivery, enhancement of counselors’ evaluation competencies, and improved collaboration with parents and external parties. These strategies are expected to support the sustainable and effective implementation of guidance and counseling services in schools.